Antivascular endothelial growth factor in the treatment of retinopathy of prematurity. Issue 5 (September 2016) - Patel, Jinali R.; Ranjan, Sinthu S.; Wasserman, Barry N.
Abstract : Purpose of review: To review the most recent literature regarding the clinical experience of antivascular endothelial growth factor (anti-VEGF) therapies in the treatment of retinopathy of prematurity (ROP). Recent findings: Anti-VEGF agents in stage 3+ and aggressive posterior ROP have been shown to induce rapid ROP regression. However, significant reoccurrence rates can require repeat injections and thus longer term and more frequent follow-up. Initial studies reflect conflicting evidence regarding significant systemic side effects of these treatments, and outcomes in these patients past the first few years of life are yet to be definitively determined. Summary: Although anti-VEGF therapies show promise in the treatment of ROP, frequent reoccurrences and lack of thorough data about long-term side effects of pharmacologic intervention necessitate further research before anti-VEGF agents become the mainstay of ROP management.